On the analytic form of the discrete Kramer sampling theorem - Antonio G. García; Miguel A. Hernández-Medina; María J. Muñoz-Bouzo (International Journal of Mathematics and Mathematical Sciences)
The classical Kramer sampling theorem is, in the subject of self-adjoint boundary value problems, one of the richest sources to obtain sampling expansions. It has become very fruitful in connection with discrete Sturm-Liouville problems. In this paper a discrete version of the analytic Kramer sampling theorem is proved. Orthogonal polynomials arising from indeterminate Hamburger moment problems as well as polynomials of the second kind associated with them provide examples of Kramer analytic kernels.